Research of control strategy for VSC-HVDC system under unbalanced grid voltage conditio - SUN Bo; ZHANG Jian-wen; PAN Lei-luo; HAN Gang (Gong-kuang zidonghua, 2013)
In view of problems of harmonic and power fluctuation of DC and AC side of VSC-HVDC system under unbalanced grid voltage condition, the paper used dual dq-PI control strategy with respective direction of positive and negative sequence components of grid voltage to inhibit the second harmonic of DC side and active power fluctuation of AC side based on establishing mathematical model of VSC in positive and negative d-q coordinate. In view of problem that traditional phase sequence decomposition is too slow, so as to influence dynamic performance and band width of the control system, it used a rapid phase sequence decomposition method. The simulation result shows that the dual dq-PI control strategy can inhibit fluctuation of DC voltage and AC current comparing with the traditional control strategy.